2021
DOI: 10.20870/ives-tr.2021.4734
|View full text |Cite
|
Sign up to set email alerts
|

Prévenir l’esca chez <em>Vitis vinifera</em> en proscrivant les modes de conduite ou les systèmes de taille mutilants

Abstract: Afin d’illustrer l’influence des modes de conduite ou des systèmes de taille, sur le développement d’une maladie du bois de la vigne, l’esca, une synthèse a été réalisée à partir de résultats obtenus dans le cadre de deux projets, le CASDAR/CNIV V1303 (2013-2017) et ‘GTDfree’ financé par l’ANR et la Maison Hennessy (2016-2021). Une conclusion majeure est que les modes de conduite extrêmement simplifiés et les systèmes de taille trop sévères sont à proscrire dans le cadre de la prévention et gestion de l’esca, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Important pruning practices include limiting the number and size of clean cuts in order to help reduce the susceptibility of the cordon to fungal trunk disease infection, as well as avoiding pruning during wet conditions when spore inoculum is prevalent [101]. It has been suggested that training methods involving minimal pruning show less esca disease effect than methods involving regular manual pruning [102], and techniques which concentrate pruning wounds on the crown of the vine should be avoided, particularly for cultivars sensitive to wood disease. Recent research has indicated that the total surface area of cuts on a cordon rather than the diameter of each cut is the more important factor in regard to incidence of Eutypa dieback [103].…”
Section: Maintenance Of Cordon Armsmentioning
confidence: 99%
“…Important pruning practices include limiting the number and size of clean cuts in order to help reduce the susceptibility of the cordon to fungal trunk disease infection, as well as avoiding pruning during wet conditions when spore inoculum is prevalent [101]. It has been suggested that training methods involving minimal pruning show less esca disease effect than methods involving regular manual pruning [102], and techniques which concentrate pruning wounds on the crown of the vine should be avoided, particularly for cultivars sensitive to wood disease. Recent research has indicated that the total surface area of cuts on a cordon rather than the diameter of each cut is the more important factor in regard to incidence of Eutypa dieback [103].…”
Section: Maintenance Of Cordon Armsmentioning
confidence: 99%